Embeddedness and perceived oneness: Examining the effects of job embeddedness and its trajectory on employee proactivity via an identification perspective. - Li, Junchao (Jason); Mitchell, Terence R.; Lee, Thomas W.; Eberly, Marion B.; Shi, Lihua (Journal of Applied Psychology, 2022)
Although job embeddedness has consistently been shown to be associated with positive workplace behaviors, our theoretical understanding of such associations remains far behind our empirical knowledge. In particular, it is unclear how job embeddedness goes beyond its common conceptualization as "stuckness" to motivate employees' discretionary, change-oriented behaviors at work. To this end, we trace the original theoretical foundation of job embeddedness theory in field theory and establish its theoretical connection to social identity theory. We propose that increased organizational identification is an intrinsic psychological mechanism through which job embeddedness motivates proactive behaviors from employees. Further informed by field theory, we also examine the implications of job embeddedness change over time. We propose that a more positive trajectory of embeddedness over time contributes to enhanced organizational identification and employee proactivity, above and beyond the absolute level of embeddedness. We report a longitudinal study that surveyed 264 employees at three points in time over the course of 1 year and provide substantial support for the hypotheses. Implications of our work are discussed. (PsycInfo Database Record (c) 2022 APA, all rights reserved).